EFFECTIVE USE OF GAMES, SONGS, MUSIC AND STORIES IN TEACHING FOREIGN LANGUAGES TO CHILDREN AND ADOLESCENTS - Yusupova Maftuna; Moydinova Shohida (TADQIQOTLAR, 2025)
Annotation: This paper explores the effectiveness of using games, songs, music, and stories in teaching foreign languages to children and adolescents. It highlights how these tools enhance motivation, improve memory, and create a positive learning environment. The paper also examines the role of these methods in developing communicative competence, cultural awareness, and creativity. Practical examples and strategies for classroom use are provided.